Evaluating student feedback on the MBBS mentorship program in a medical college - Shah Mohammad Abbas Waseem; Ali Jafar Abedi; Syed Haider Mehdi Husaini (Zanjan University of Medical Sciences and Health Services, 2024)
Background & Objective: Mentorship is essential for medical undergraduates' professional and personal development to enhance soft skills, knowledge, and academic performance. The present study analyzed the mentee's feedback about the program. Material & Methods: The present cross-sectional (retrospective) study, approved by the ethics committee, was conducted between January and March 2022. One hundred fifty feedback forms (open and closed-ended questions) of 2016-2019 MBBS students (at the end of one and a half years of implementation) were analyzed. Data were represented as mean±SD and median. Qualitative data was coded and analyzed descriptively. Results: 58 % and 50.66% of mentees agreed on easy approachability and communication with mentors. 52.67 % agreed strongly, and 52% agreed that mentors listened actively to their problems and provided constructive feedback. 68.67% agreed and 56.67% agreed strongly that important lessons about personal, college, and career life were learned. 78.66% agreed that research motivation was provided. 71, 33%, and 60% agreed that mentoring helped improve academics and develop a conceptual learning style. 70% and 51.33% agreed that mentors helped them solve medical life problems and develop skills (communication, interpersonal, and humane values). 46.66% agreed that mentors encouraged them to participate in sports or extracurricular activities. 52% agreed strongly that their mentors had a professional attitude, 47.33% agreed mentors were beneficial to them, and 46.67% agreed strongly to recommend their mentors for future professional and personal development activities. Open-ended analysis showed that, in decreasing order, the most beneficial developmental activities performed with their mentors were problem-solving (40.56%), guidance, counseling (34.26%), and soft skill development (13.85%). Menttes considered time constraints a hurdle and suggested scheduled, regular meetings and the use of social media for the program's effectiveness. Conclusion: Regular feedback, evaluation, and perceptions of mentees are vital for the mentorship program.